Thermodynamics of Mg–Al Order-Disorder Reaction in MgAl2O4-Spinel: Constrained by Prolonged Annealing Experiments at 773–1123 K - Yunlu Ma; Xinjian Bao; Xi Liu (Molecules, 2021)
MgAl2O4-spinel has wide industrial and geological applications due to its special structural and physical–chemical features. It is presumably the most important endmember of complex natural spinel solid solutions, and therefore provides a structural model for a large group of minerals with the spinel structure. There exists a well known but still inadequately understood phenomenon in the structure of MgAl2O4-spinel, the Mg–Al cations readily exchanging their positions in response to variations of temperature, pressure, and composition. A large number of experiments were performed to investigate the Mg–Al cation order-disorder process usually quantified by the inversion parameter x (representing either the molar fraction of Al on the tetrahedral T-sites or the molar fraction of Mg on the octahedral M-sites in the spinel structure), and some thermodynamic models were thereby constructed to describe the x-T relation. However, experimental data at some key T were absent, so that the different performance of these thermodynamic models could not be carefully evaluated. This limited the interpolation and extrapolation of the thermodynamic models. By performing some prolonged annealing experiments with some almost pure natural MgAl2O4-spinel plates and quantifying the x values with single-crystal X-ray diffraction technique, we obtained some critical equilibrium x values at T down to 773 K. These new x-T data, along with those relatively reliable x values at relatively high T from early studies, clearly indicate that the CS94 Model (a model constructed by Carpenter and Salje in 1994) better describes the Mg–Al cation order-disorder reaction in MgAl2O4-spinel for a wide range of T. On the basis of the CS94 Model, a geothermometer was established, and its form is T-closure = 21362 × x3 − 12143 × x2 + 6401 × x − 10 (T-closure standing for the closure temperature of the Mg–Al cation exchange reaction). This geothermometer can be used to constrain the thermal history of the geological bodies containing MgAl2O4-spinel.